2017
DOI: 10.1080/19336934.2017.1409927
|View full text |Cite
|
Sign up to set email alerts
|

FijiWingsPolarity: An open source toolkit for semi-automated detection of cell polarity

Abstract: Epithelial cells are defined by apical-basal and planar cell polarity (PCP) signaling, the latter of which establishes an orthogonal plane of polarity in the epithelial sheet. PCP signaling is required for normal cell migration, differentiation, stem cell generation and tissue repair, and defects in PCP have been associated with developmental abnormalities, neuropathologies and cancers. While the molecular mechanism of PCP is incompletely understood, the deepest insights have come from Drosophila, where PCP is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The point mutations that lead to loss of binding to a single effector (Y374F only binding Dsh, and V376A only binding to Pk) showed a weaker phenotype as compared to Y374A (Figure 4C-D). This was further supported through quantification of cellular hair orientation, using the FijiWingsPolarity plug-in (Dobens et al, 2018), that revealed a significant variation from the Vang WT control in each case, and also between Vang-Y374A and the other point mutations (Figure 4C-D). Importantly, the difference in phenotype was not due to variation in expression levels, as all genotypes showed equivalent protein levels in larval disc lysates (Figure 4E).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…The point mutations that lead to loss of binding to a single effector (Y374F only binding Dsh, and V376A only binding to Pk) showed a weaker phenotype as compared to Y374A (Figure 4C-D). This was further supported through quantification of cellular hair orientation, using the FijiWingsPolarity plug-in (Dobens et al, 2018), that revealed a significant variation from the Vang WT control in each case, and also between Vang-Y374A and the other point mutations (Figure 4C-D). Importantly, the difference in phenotype was not due to variation in expression levels, as all genotypes showed equivalent protein levels in larval disc lysates (Figure 4E).…”
Section: Resultsmentioning
confidence: 69%
“…( D ) Quantification of the percentage of cellular actin hairs oriented within a specific angle range for the indicated genotypes. Angles were determined using plugin FijiWingsPolarity (Dobens et al 2018). Cellular hair orientation angles from 3 independent wings were combined, and data binned for statistical analysis via Chi-squared test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some are only executable on certain operating systems (e.g. FijiWingsPolarity [40], which works with Mac OS, but not PC). Of those that remain, the underlying approaches to measuring cell orientation differ from PCPA.…”
Section: Discussionmentioning
confidence: 99%
“…In the fly, the cells of various body parts and appendages are polarized in the proximal-distal direction. This polarity is easily recognized by the orientation of actinbased hairs, formed at the posterior of individual epithelial cells of the wing, notum, and legs [4]. Two main PCP pathways organize proximal-distal polarity in various tissues.…”
Section: Pcp Basicsmentioning
confidence: 99%